EFEK MEDIASI MOTIVASI KARYAWAN PADA PENGARUH PELATIHAN DIGITAL DAN PENILAIAN KINERJA DIGITAL TERHADAP KINERJA KARYAWAN - Budhi Herlambang, Vikram; Agung Maryudi Harsiwi, Theresia (Penerbit Lafadz Jaya, 2025)
This research aims to analyze the influence of digital training and digital performance appraisal on employee performance, as well as to analyze the mediating role of work motivation in the influence of digital training and digital performance appraisal on employee performance. The success of digital transformation does not solely depend on technology itself, but also on the psychological aspects of employees. Advanced technology will not be effective if employees do not feel motivated to use it. This research employs quantitative design with a survey method conducted on 56 company employees selected through purposive sampling with a minimum tenure criterion of 1 year. Questionnaires were distributed online and analyzed using Structural Equation Modeling (SEM) to test the relationships between the research variables. The results show that digital training has no significant effect on employee motivation, digital performance appraisal has a significant and positive effect on employee motivation, employee motivation has a significant and positive effect on employeeperformance, while employee motivation does not mediate the effect of digital training on employee performance, while employee motivation mediates the effect of digital performance appraisal on employee performance.